Characterization of synthetic wheat line Largo for resistance to stem rust. Issue 8 (4th June 2021) - Sharma, Jyoti Saini; Overlander, Megan; Faris, Justin D; Klindworth, Daryl L; Rouse, Matthew N; Kang, Houyang; Long, Yunming; Jin, Yue; Lagudah, Evans S; Xu, Steven S
Abstract: Resistance breeding is an effective approach against wheat stem rust caused by Puccinia graminis f. sp . tritici ( Pgt ). The synthetic hexaploid wheat line Largo (pedigree: durum wheat "Langdon" × Aegilops tauschii PI 268210) was found to have resistance to a broad spectrum of Pgt races including the Ug99 race group. To identify the stem rust resistance ( Sr ) genes, we genotyped a population of 188 recombinant inbred lines developed from a cross between the susceptible wheat line ND495 and Largo using the wheat Infinium 90 K SNP iSelect array and evaluated the population for seedling resistance to the Pgt races TTKSK, TRTTF, and TTTTF in the greenhouse conditions. Based on genetic linkage analysis using the marker and rust data, we identified six quantitative trait loci (QTL) with effectiveness against different races. Three QTL on chromosome arms 6AL, 2BL, and 2BS corresponded to Sr genes Sr13c, Sr9e, and a likely new gene from Langdon, respectively. Two other QTL from PI 268210 on 2DS and 1DS were associated with a potentially new allele of Sr46 and a likely new Sr gene, respectively. In addition, Sr7a was identified as the underlying gene for the 4AL QTL from ND495. Knowledge of the Sr genes in Largo will help to design breeding experiments aimed to develop new stem rust-resistant wheat varieties. Largo and its derived lines are particularly useful for introducing two Ug99-effective genes Sr13c and Sr46 into modern bread wheat varieties. The 90 K SNP-based high-density map will be useful for identifying the other important genes in Largo.